Application Of Digital Learning And Interactive Tools For Boosting Modern Constructivist Pedagogies Case Of Western Algerian Universities - Chib, Djazia Amina; Zine, Younes (جامعة الوادي - University of Eloued, 2024)
In view of the technological changes with the tools and teaching methods used, elearning has become a priority and challenge for the University of Algeria. This article recommends the use of basic teaching principles, which take into account the broad teaching principles of scientific content, visualization, and accessibility. And the feasibility of education, the humanization of education, awareness-raising and student participation. These principles have been modified to meet the needs of digital learning. Using quantitative methods as survey data collection to answer the research question, three main directions for the development of digital learning systems are proposed: constructivist teaching method; the degree of teacher-student interaction; and digital learning environment. The use of active teaching methods and the use of interactive tools to allow students to actively participate in learning has stimulated students' great interest and improved the quality of learning
مقال
Keywords: constructivist pedagogy ; boosting ; digital learning ; interactive tools ; Algerian universities